2020
DOI: 10.12911/22998993/123473
|View full text |Cite
|
Sign up to set email alerts
|

Spring Row Crops Productivity Prediction Using Normalized Difference Vegetation Index

Abstract: The results of statistical modelling for the yields prediction of spring row crops, namely, maize, sorghum and soybean, depending on the values of the remotely sensed normalized difference vegetation index (NDVI) at critical stages of the crops growth and development were presented. The spatial NDVI data obtained from the Sentinel-2 satellite were used to create the models. Quadratic regression analysis was applied to develop the yielding models based on true yield data of the crops obtained in the period of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…[ 2 ]. For example, crop producers can easily predict their yields in advance to harvesting period just using the average field NDVI values and simple gradual scales or models that is of great importance for crop production sector of the economy [ 4 ]. Therefore, most farmers are longing to have access to NDVI data.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 ]. For example, crop producers can easily predict their yields in advance to harvesting period just using the average field NDVI values and simple gradual scales or models that is of great importance for crop production sector of the economy [ 4 ]. Therefore, most farmers are longing to have access to NDVI data.…”
Section: Introductionmentioning
confidence: 99%
“…However, as biomass density increases, NDVI becomes saturated [ 66 , 67 ]. NDVI data accurately explained the variation of sorghum yield [ 68 , 69 ] (maize GY [ 70 , 71 ] and teff GY [ 72 ] in previous researches.…”
Section: Resultsmentioning
confidence: 88%
“…The reported yield values were regressed against the NDVI data, and they found that MODIS-NDVI data could effectively predict crop yield for the Tisza river catchment area 6-8 weeks before harvest. Similarly, Lykhovyd (2020) and Vozhehova et al (2020) applied NDVIbased regression models for forecasting yield of spring row crops at the field scale. The combination of crop models and remote sensing data has increasingly been used to forecast crop yield.…”
Section: Introductionmentioning
confidence: 99%